Appendiceal vesical fistula first presenting as giant bladder calculi: A case report and review of literature - Chen Wang; Ye Wu; Xianya He; Guangqing Song; Yuanwei Li; Qiang Lu (Urology Case Reports, 2024)
A 34-year-old man was admitted to the hospital presenting repeatedly urinary urgency for 3 years and yellow-green lithotripsy foreign body in urine for 1 month. Initially, he was diagnosed with a giant bladder calculi. After a cystoscopy exam and a lithotripsy for bladder calculi, Appendiceal vesical fistula was finally diagnosed and treated with a laparoscopic surgery. We report a rare case of appendiceal vesical fistula，first presenting as giant bladder calculi，and successfully treated with minimal invasive surgery We report this case and reviewed literature to improve the understanding of this disease and reduce misdiagnosis and missed diagnosis.